Doing theology through reception studies: Towards a post-postmodern theological hermeneutics - Wisse, Maarten (Nederduitse Gereformeerde Teologiese Tydskrif, 2012)
In this paper, I propose a new approach to the role of the Bible in systematic theology. I take my starting point in the contemporary clash between those who follow the Enlightenment disintegration of Scripture, and conservative attempts to do theology on the basis of Scripture as the infallible Word of God. Subsequently, I present my research project into the reception of John as a way of pursuing insights from all major stages of the history of theological hermeneutics. A deconstructive reading of pre-modern use of the Bible shows that it is much more sensitive to diverging voices in Scripture than is often assumed. Scrutinizing the reasons that pre-modern theologians have for privileging John over Paul or the other way around, brings up theological motives that become fresh material for doing theology today.